The Composition of A Moment of Everything - Carter, Jackson (Tufts Archival Research Center, 2023)
A Moment of Everything is a piece of music for full orchestra I wrote over the last year, which was performed by the Tufts Symphony Orchestra on April 18th, 2023. This essay chronicles the process of composing the piece, details its unique structure, and examines the music theory behind it. The full score of the piece itself is included at the end of the essay.; Thesis (B.A.)--Tufts University, 2023.; Submitted to the Dept. of Music.